Economies of scope, modularity and property rights in software technologies - Özaygen, Altay (Université Evry-Val-d’Essonne, 2013)
Cette thèse étudie le rôle des différents régimes de propriété intellectuelle (DPI) et évalue ses conséquences sur l'industrie du logiciel. En outre, ce travail porte sur l'équilibre entre deux modèles de logiciels, celui des logiciels privés et celui des logiciels libres et open source, et cherche à évaluer leurs effets sur la performance des entreprises. Ainsi nous discutons dans un premier article les facteurs clés de la cinquième révolution technologique à travers le concept de paradigme technoéconomique (Freeman et Perez, 1988) et nous considérons l'open source comme le principal de ces facteurs. D'autre part, nous étudions les trois aspects des technologies logicielles. Les caractéristiques structurelles des logiciels, c'est-a-dire les économies de gamme (Panzar et Willig, 1981; Teece, 1980) et la modularité (Parnas, 1972; Langlois et Robertson, 1992) représentent les deux premiers. Le régime de propriété intellectuelle, qui est a l'origine des particularités institutionnelles du logiciel (Mazzeloni et Nelson, 1998b), représente le troisième aspect. Au sein de cette thèse nous utilisons différentes méthodologies et considérons plusieurs technologies logicielles pour répondre à nos questions de recherches. Les économies de gamme de logiciels sont étudiées à travers une simulation multi-agents. La recherche sur la modularité est effectuée par une analyse des brevets sur la technologie d'indexation de vidéo. La question des DPI est examinée dans deux chapitres différents. Dans un premier chapitre, une analyse de données de panel est faite pour démontrer l'effet du brevetage et de la contribution au projet du noyau Linux sur la performance des entreprises. Le second chapitre traite quant à lui d'un cas particulier où l'innovation ouverte est réalisée par un groupe de recherche en ingénierie du logiciel au sein d'Alcatel-Lucent Bell Labs, Nozay, France. Ces exemples uniques ne peuvent conclure sur aucune tendance macro sur l'industrie du logiciel, mais cette thèse vise à alimenter les discussions sur les droits de propriété intellectuelle au sein de l'industrie du logiciel.
Keywords: Analyse de brevets; Industrie -- Logiciels; Intellectual property; Logiciels libres; Modularity; Open source; Propriedade intelectual; Propriété intellectuelle; Software industry

Copyright : rebalancing the public and private interests in the areas of education and research - Wang, Jia (Stellenbosch University, 2013)
The general public should have wide access to copyrighted materials for education and research. However, since the current copyright law system subtly favors copyright holders, it is time to re-evaluate copyright law to ensure it meets its original purpose of promoting the learning of the society. The research primarily focuses on how to broaden copyright limitations and exceptions for the public to access and use learning materials. Within the framework of the copyright law system, other mechanisms that allow users to access copyrighted materials at a reasonable price also are considered. Such mechanisms include an efficient collective copyright management system and various licensing schemes. In an information network environment, it is time for developing countries to reform copyright law in order to promote education and research. It is hoped the findings of this study not only benefit South Africa and People's Republic of China, but also provide insights and guidelines to other developing countries with similar conditions.
Keywords: China; Copyright; Economic aspects; Education and copyright law; Effect of copyright on ICT; Freedom of information and opinion; Globalization and education; Information and communication technology; Intellectual property; South Africa

Open-source software and the rationale for copyright protection of computer programs - Karjiker, Sadulla (Stellenbosch University, 2013)
The rationale for the legal protection of copyright works is based on the perceived need to encourage the creation of works which are considered to be socially beneficial. By awarding authors proprietary rights in their creations, copyright law allows authors the ability to earn direct financial returns from their efforts, and, thus, copyright law provides the required incentives for authors to create copyright works. Since the early days of commercial software development, copyright protection has been extended to computer programs; thus, by providing such protection it was assumed that their production should be encouraged, and that without such protection they will not be produced to the extent required by society. Comparatively recently, we have witnessed large-scale production of open-source software, which is licensed on generous terms, giving users the right to freely use, modify and redistribute such software. By adopting such licensing terms, the authors of open-source software are unable to charge licensees a fee for permission to use their software, which is the reward which copyright assumes authors seek to create such software. This development has made it necessary to re-evaluate the rationale for copyright protection of computer programs, and determine whether the continued protection of computer programs is justifiable. This study seeks to first establish a coherent theoretical justification for copyright protection, which it is submitted should be an economic justification, rather than a moral justification. The legal analysis in this work seeks to establish whether the copyright protection of computer programs is consistent with the economic justification for copyright protection. In particular, the analysis focuses on the current scope of copyright protection, and seeks to establish whether such protection is excessive, stifling creativity and innovation, and, thus, imposing too high a social cost. It is contended that copyright doctrine has generally sought to minimise these costs, and that current scope of copyright protection of computer programs leaves enough creative room for the production of new software. Despite the fact that the effect of open-source software licences is that authors are unable to earn the direct financial rewards which copyright enables authors to earn as an incentive to create such software, their authors continue to have financial incentives to create such software. Commercial firms who invest in open-source software do so because they seek to provide financially-rewarding related services in respect of software, or because it serves to promote sales in their complementary products. Similarly, the participation of individual computer programmers is largely consistent with the standard economic theories relating to labour markets and the private provision of public goods. Individuals are principally motivated by economic motives, such as career concerns. Copyright protection gives participants the choice to opt for the direct financial rewards which its proprietary protection enables, or the more indirect financial rewards of open-source software development. It is submitted within this research that rather than undermining the rationale for copyright protection of computer programs, the development of open-source software has illustrated that copyright protection allows for the emergence of alternative business models, which may be more economically advantageous to authors.
Keywords: Computer programs; Copyright law; Intellectual property; Open-source software

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification